(untitled) (Dhaka University Journal of Biological Sciences, 2019)
The present study intends to investigate the medium-term effect of early life weather shock on non-verbal intelligence of SIDR affected children. The hypothesis was, the nonverbal IQ of SIDR affected children would be lower than the non-verbal IQ of SIDR non-affected children. For this purpose, 60 students of grade 4 - 5 were selected as respondents. Among them half of the respondents were from SIDR affected area and remaining were from non-affected area. In order to measure non-verbal intelligence, Test of Non-verbal Intelligence-2 (TONI-2) was administered which was developed by Brown et al. (1990). Independent-sample t-test was employed to compare the non-verbal intelligence of the participants in SIDR affected and SIDR non-affected conditions. The result shown that there is a significant difference on non-verbal intelligence between affected and non-affected samples and the nonverbal intelligence (IQ) of SIDR affected children is significantly lower than the non-verbal intelligence (IQ) of non-affected participants. Dhaka Univ. J. Biol. Sci. 28(1): 61-69, 2019 (January)